2015
DOI: 10.1007/s13312-015-0607-0
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based surveillance of invasive pneumococcal disease and pneumonia in South Bangalore, India

Abstract: Objective:To estimate the incidence of invasive pneumococcal disease and pneumonia, distribution of pneumococcal serotypes, and antibiotic susceptibility in children aged 28 days to <60 months. Design: Hospital-based surveillance.Setting:; South Bangalore, India.Participants: 9950 children aged 28 days to <60 months with clinical suspicion of invasive pneumococcal disease or pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Several studies showed that S. pneumoniae was most common organism (30–50%) [Capoor et al 2006; Farooqui et al 2015; Rudan et al 2013; Mathew et al 2015; Tiewsoh et al 2009; Awasthi and Pande, 1997; Pandey et al 2000; Bahl et al 1995] followed by H. influenzae type b in 8.8% [Capoor et al 2006] and Staphylococcus aureus 7–23% [Capoor et al 2006; Tiewsoh et al 2009; Pandey et al 2000]. In Indian children, different serotypes of S. pneumoniae were isolated with serotypes 1 and 5 being most prevalent followed by 4, 6A and 6B, 7, 12, 14, 15, 19F, 23, and 45 [Nisarga et al 2015; Balaji et al 2015; John et al 1996; Kurien et al 1999; Kanungo and Rajalakshmi, 2001].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies showed that S. pneumoniae was most common organism (30–50%) [Capoor et al 2006; Farooqui et al 2015; Rudan et al 2013; Mathew et al 2015; Tiewsoh et al 2009; Awasthi and Pande, 1997; Pandey et al 2000; Bahl et al 1995] followed by H. influenzae type b in 8.8% [Capoor et al 2006] and Staphylococcus aureus 7–23% [Capoor et al 2006; Tiewsoh et al 2009; Pandey et al 2000]. In Indian children, different serotypes of S. pneumoniae were isolated with serotypes 1 and 5 being most prevalent followed by 4, 6A and 6B, 7, 12, 14, 15, 19F, 23, and 45 [Nisarga et al 2015; Balaji et al 2015; John et al 1996; Kurien et al 1999; Kanungo and Rajalakshmi, 2001].…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-seven strains were isolated from children 21 to 60 months old with serotypes 6B and 7F as the most dominant types. Other Indian studies 28,30,33 have also reported isolation of S. pneumoniae from young children 20 months old with serotype 6 as the most prevalent isolate. Serotypes 1 and 18 were identified as the most common isolates in children older than 20 months and younger than 60 months.…”
Section: Discussionmentioning
confidence: 85%
“…25,26 The predominant serotypes detected in this study were type 1, followed by serotypes 6B and 14, which accounted for 35% of all invasive isolates. Studies from South India 27,28 have reported 14, 5, 1 and 6A, 14, 5 as the most common serotypes correspondingly.…”
Section: Discussionmentioning
confidence: 96%
“…However, their implementation has not yet begun, 22 possibly highlighting the disconnect between health research, policy, and government funding. India is 1 of 75 countries receiving Global Alliance for Vaccine and Immunizations assistance for implementation of PCV into the national immunization schedule.…”
Section: Resultsmentioning
confidence: 99%